Content-Based Instruction Approach In Instructional Multimedia For English Learning - Farani, Rizki (English Education Department, Universitas Islam Indonesia, 2012)
Content-based Instruction (CBI) is an approach in English learning that integrates certain topic and English learning objectives. This approach focuses on using English competencies as a “bridge” to comprehend certain topic or theme in English. Nowadays, this approach can be used in instructional multimedia to support English learning by using computer. Instructional multimedia with computer system refers to the sequential or simultaneous use of variety of media formats in a given presentation of selfstudy program in a computer. Instructional media combines several aspects such as text, pictures, graphic, sound and video. There are many English materials that are presented in a computer display by combining all aspects of multimedia. This method can help learner to understand the material better by visualizing the concept. In integrating CBI approach in instructional multimedia by using computer, there are two important aspects in creating effective multimedia, such as displaying reading text and integrating all English skills. In displaying reading text, CBI approach play important role in presenting reading passages about certain topic based on students' interest and multimedia aspects also play significant role in visualizing all concepts and vocabularies from the reading passage. This paper will discuss the integration of CBI approach in instructional multimedia for English learning deeply by presenting the basic concept and providing some examples of instructional multimedia display.Keywords: Content-Based Instruction Approach, Instructional Multimedia, English Learning